2012
DOI: 10.4171/lem/58-1-1
|View full text |Cite|
|
Sign up to set email alerts
|

Exemples de variétés projectives strictement convexes de volume fini en dimension quelconque

Abstract: Résumé. -Nous construisons des exemples de variétés projectives Ω Γ proprement convexes de volume fini, non hyperbolique, non compacte en toute dimension n ⩾ 2. Ceci nous permet au passage de construire des groupes discrets Zariski-dense de SL n+1 (R) qui ne sont ni des réseaux de SL n+1 (R), ni des groupes de Schottky. De plus, l'ouvert proprement convexe Ω est strictement convexe, même Gromov-hyperbolique.Abstract. -We build examples of properly convex projective manifold Ω Γ which have finite volume, are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The thick-thin decomposition was obtained in dimension 2 by Choi [16], where he asked if it could be extended to arbitrary dimensions. During the course of this work, Choi obtained some results similar to some of ours (see [19]), and we learnt of Marquis [41], [40], [39] who has studied finite area projective surfaces and constructed examples of cusped non-hyperbolic real projective manifolds in all dimensions. Recently he and Crampon proved a Margulis lemma [25].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The thick-thin decomposition was obtained in dimension 2 by Choi [16], where he asked if it could be extended to arbitrary dimensions. During the course of this work, Choi obtained some results similar to some of ours (see [19]), and we learnt of Marquis [41], [40], [39] who has studied finite area projective surfaces and constructed examples of cusped non-hyperbolic real projective manifolds in all dimensions. Recently he and Crampon proved a Margulis lemma [25].…”
supporting
confidence: 53%
“…Therefore there is no bound on the number of isometry (= projective equivalence) classes of strictly convex manifolds with bounded volume. Marquis has similar examples for hyperbolic manifolds with cusps [41].…”
Section: Topological Finitenessmentioning
confidence: 90%
“…Further work of Benoist [4] shows that these structures are actually strictly convex. In the non-compact case, recent work of Marquis [20] has shown that the projective structures arising from bending remain properly convex in this setting as well.…”
Section: Introductionmentioning
confidence: 95%
“…The corresponding geometric structures have been shown to be properly convex for manifolds that are closed [40] and compact [42]. In the closed case Benoist showed that the structures are in fact strictly convex [8].…”
Section: Rigidity Of Convex Projective Structures On a Manifold Or Orbifoldmentioning
confidence: 99%